Hazard-Driven Drivers’ Behaviours towards Vehicle-to-Median Safe Distances - Siregar, Martha Leni (Makara Journal of Technology, 2015)
A median is required for a two-way road to separate traffic from opposing lanes and to prevent head-on collisions. However, studies indicate that medians are also perceived as hazards which need to be avoided during driving. This hazard perception is manifested in drivers’ changing behavior towards various types of medians along the driving lanes inform of their tendency to allow various safe distances to the medians. The Indonesian Highway Capacity Manual (IHCM) does not differentiate between types of medians and the influence on the drivers’ choice of safe margin to the medians. Therefore, this study looks into how the existence and types of medians influence the safety distances of different categories of vehicles from different types of medians as the manifestation of their perception of hazard potentials of medians. Traffic recordings on different categories of vehicles are used to obtain movement margins of vehicles along various medians during near-saturated traffic. Using the smallest values of 10 and 90 percentile of distances, the results show that drivers shy from 0.27 m to 0.82 m from medians. The result of this study will contribute to the change of applied assumptions used in determining the effective lane capacity to road safety-based assumptions.